Emergency Surgery during Lockdown: Experience at a tertiary care hospital - Muhammad Waqas Raza ,Muhammad Zafar Iqbal ,Malik Irfan Ahmed ,Tariq Nawaz (Journal of Rawalpindi Medical College, 2020)
Introduction: COVID-19 has halted the economic and social progression of the human race. This pandemic has exposed the vulnerabilities of all walks of life. But, most of all, this crisis has jolted the health care systems around the globe. A decrease in emergency surgical interventions was observed at District headquarters Hospital, Rawalpindi. The purpose of this study was to evaluate the impact of a pandemic on acute surgical emergency presentation and referral to a tertiary care hospital. Material and Methods: It is a retrospective cohort study. We compared emergency surgical interventions requiring spinal or general anaesthesia followed by admission in a ward at DHQ hospital, Rawalpindi during a control period (15th March 2019–15th June 2019) and during the pandemic lockdown period (15th March 2020- 15th June 2020). Results: A total of 228 cases were included in the study including both groups. About 73% (167 ) cases were performed in an emergency during Pre COVID-19 period i.e. from March 15th- June 15th, 2019. A total of 41 exploratory laparotomies were performed in a total of which 28 (68%) were done in the control period while 13 (32%) were done during the lockdown period. Out of 13 laparotomies due to road traffic accidents, only 3 were done during the lockdown period. Civilian Violence causing penetrating trauma resulted in 21 laparotomies in total out of which 11 were before the COVID-19 crisis and 10 during the lockdown. A total of 107 appendectomies were performed. Out of which 75 (70%) were performed in the Pre COVID-19 pandemic. Less than half the number (32) of appendectomies were done during the lockdown. A marked decrease in emergency hernia surgeries was observed. In the Pre COVID-19 time period, 13 emergency hernia surgeries were done, while only 03 surgeries were done during the lockdown. Regarding Hepatobiliary emergency surgeries, none was done during lockdown while 08 were done during three months of the Pre COVID-19 period. Conclusion: Firstly, Keeping these figures under consideration, surgical units should expect more complicated cases in the coming days and a high influx of patients should be expected once the lockdown is over. Secondly, the question that remains unanswered is that Are we doing unnecessary surgeries other than trauma in an emergency? Thirdly, there is room to consider that all appendicitis and cholecystitis don’t always need surgery. Fourthly, the private sector has the potential to share the burden on public hospitals.